2022
DOI: 10.1039/d1dt03624f
|View full text |Cite
|
Sign up to set email alerts
|

One-pot synthesis of stable and functional hydrophilic CsPbBr3 perovskite quantum dots for “turn-on” fluorescence detection of Mycobacterium tuberculosis

Abstract: All-inorganic CsPbBr3 perovskite quantum dots (QDs) are widely studied owing to their excellent optoelectronic properties, however they are usually hydrophobic and unstable in water that seriously limit their biomedical applications....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…When using OA and OAm surface ligands to modify CsPbBr 3 PNCs, the LARP method is simple and does not require high experimental environment. 32 Therefore, OA-OAm-CsPbBr 3 (LARP) is synthesized by LARP using OA and OAm ligands. The microstructures are characterized by TEM and HRTEM.…”
Section: Morphology and Structure Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…When using OA and OAm surface ligands to modify CsPbBr 3 PNCs, the LARP method is simple and does not require high experimental environment. 32 Therefore, OA-OAm-CsPbBr 3 (LARP) is synthesized by LARP using OA and OAm ligands. The microstructures are characterized by TEM and HRTEM.…”
Section: Morphology and Structure Characterizationmentioning
confidence: 99%
“…Figure 1f shows the XRD characterization results of OA-OAm-CsPbBr 3 (LARP) and OA-OAm-CsPbBr 3 @SiO 2 (LARP). The diffraction peaks at 15.2°, 21.5°and 30.7°correspond to the (100), ( 110) and (200) crystal faces in the standard XRD card of CsPbBr 3 (PDF#18−0364), 34 indicating that SiO 2 coating does not change the crystal structure of OA-OAm-CsPbBr 3 (LARP). The experimental results show that OA-OAm-CsPbBr 3 (LARP) and OA-OAm-CsPbBr 3 @SiO 2 (LARP) are synthesized successfully, but the size of OA-OAm-CsPbBr 3 (LARP) is not uniform and there is a problem that OA-OAm-CsPbBr 3 @SiO 2 (LARP) contains multiple nuclei in one shell.…”
Section: Morphology and Structure Characterizationmentioning
confidence: 99%
“…This is an inspiring work in detecting PA in water. Through a one-pot synthetic method, stable carboxyl group-functionalized CsPbBr 3 –COOH QDs were developed by using amino-poly(ethylene glycol)-carboxyl and perfluorooctyltriethoxylsilane as ligands and were engaged in the PL “turn-on” detection of Mycobacterium tuberculosis (Mtb) [ 188 ].…”
Section: Cspbx 3 (X = CL Br and I) And Composites ...mentioning
confidence: 99%
“…In another study, hydrophilic CsPbBr 3 quantum dots were functionalized using carboxyl groups and used as a biosensor for DNA detection of Mtb . The study showed low LOD of this biosensing system (51.9 pM) and was also efficient in the detection of drug resistant strains [ 179 ].…”
Section: Nanomaterials For Tb Diagnosticsmentioning
confidence: 99%